Photothermal effect by NIR-responsive excretable ultrasmall-in-nano architectures. Issue 3 (8th March 2019) - Cassano, Domenico; Santi, Melissa; D'Autilia, Francesca; Mapanao, Ana Katrina; Luin, Stefano; Voliani, Valerio
Abstract : Here, we report: (i) the straightforward production of narrow-NIR-absorbing gold ultrasmall-in-nano architectures ( t NAs), and (ii) their suitability as excretable platforms for photothermal therapy upon CW-irradiation at 808 nm. These findings are a significant step toward the translation of metal nanotheranostics to cancer treatments. Abstract : Photothermal therapy (PTT) is a promising (co)treatment with translation potentiality in oncology. Nowadays, the plasmonic nanoparticle-mediated photothermal effect (PT) relies on two well established NIR-responsive platforms: gold nanorods and nanoshells. Nonetheless, these nanostructures are affected by: (i) re-shaping after irradiation that prevents multiple PT treatments, and (ii) severe limitations to clinical translation due to metal persistence issues. Furthermore, evaluation of nanoparticle performance is usually accomplished in vitro or in mouse models, reducing the translational potential of the findings. Here, we report both the straightforward production of narrow-NIR-absorbing gold ultrasmall-in-nano architectures ( t NAs) and their suitability as platforms for PT upon CW-irradiation at 808 nm. PT efficiency is fully assessed against 2D cell cultures and customized 3D pancreatic adenocarcinoma models. Remarkably, the morphology of the t NAs is not affected by laser irradiation, allowing for repeated PT cycles and preserving their ability to avoid long-term body persistence in excretory system organs.